Bracon planitibiae sp. nov. (Hymenoptera: Braconidae), a new parasitoid of Asian longhorned beetle (Anoplophora glabripennis) - Cao, Liang-Ming; Wang, Xiao-Yi; Gould, Juli-Ruth; Li, Fei; Zhang, Yan-Long; Yang, Zhong-Qi (Zootaxa, 2019)
Bracon planitibiae sp. nov. (Hymenoptera, Braconidae), a new species parasitizing first instar larvae of Asian longhorned beetle, Anoplophora glabripennis (Motschulsky), (Coleoptera: Cerambycidae), is described. Its host is a serious wood boring pest in China, North America and Europe, where it causes severe damages to plantations of Acer spp., Populus spp., Salix spp., Ulmus spp., and many other ornamental and forest tree species. We obtained a variety of parasitoid species by using Asian longhorned beetle–infested sentinel logs to attract natural parasitoids, of which B. planitibiae sp. nov. is one. Detailed photographs of the new species are provided.